PERANAN HUKUM DALAM PEMBERANTASAN KORUPSI (KASUS PENYELEWENGAN PENYELENGGARA NEGARA DI BEBERAPA TEMPAT) - Isnawati Isnawati (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
The aim of this research is to know the role of the politics towards the good governance.The background of it is that the coruption in many countries including Indonesia has been carried out by most of the state officers. For examples (1). The governor of Banten provinc , (2). The head of Mining Officer Service in Nunukan and the Secretary of Samarinda Municipal. The method of the research is library research by getting data from mass-media either printed like news paper , magazine, brosoure or electronics like television, internet, website and twitter. The results of the research are that Ratu Atut has corrupted the health equipment in Bnaten, Azis has been bribed by Bruneian businesman, H.Ibrahim of the project of road in th boarder area in Nunukan and Fadly Illa has been marked up of the land price in Samarinda. The suggestions it is minimize the corruption are (1). To supervise continuelly on the public affairs (2). To make the good governance (3). To effort the supremacy of law.